Implementasi Filsafat Pendidikan Teknologi Kejuruan dalam Desain Kurikulum dan Pembelajaran - Adrita Gusdila; Fauzia Salmi; Rifka Jalal; Nizwardi Jalinus; Jonni Mardizal (Departement of Mathematics Education, 2024)
This study aims to examine the implementation of the philosophy of vocational technology education in curriculum design and learning in Vocational High Schools (SMK). The method used is a literature review that analyzes various sources related to the philosophy of education, curriculum, and learning practices in the field of vocational technology. The results of the study indicate that the philosophy of vocational technology education emphasizes the development of practical skills that are relevant to industry needs, as well as the integration of technical knowledge and character. The resulting curriculum must be able to accommodate the needs of the world of work, with an emphasis on project-based learning and problems that involve direct experience. Technology plays an important role in learning, allowing students to access materials flexibly and in depth. The discussion in this study concluded that the main challenges in implementing this philosophy-based curriculum are limited facilities, teacher training, and industry involvement. Therefore, close cooperation is needed between schools, government, and industry to ensure that the curriculum remains relevant and effective in preparing students to face an increasingly technology-based world of work. Optimal implementation of the philosophy of vocational technology education can improve the quality of education in SMK and prepare competent graduates.